2001
DOI: 10.1002/ana.1012
|View full text |Cite
|
Sign up to set email alerts
|

Animal model of axonal Guillain-Barré syndrome induced by sensitization with GM1 ganglioside

Abstract: Some humans develop the axonal form of Guillain-Barré syndrome after receiving bovine brain ganglioside. On sensitization with the ganglioside mixture, all of a group of rabbits injected developed high anti-GM1 IgG antibody titers, flaccid limb weakness of acute onset, and a monophasic illness course. Pathological findings for the peripheral nerves showed predominant Wallerian-like degeneration, with neither lymphocytic infiltration nor demyelination. IgG was deposited on the axons of the anterior roots, and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(175 citation statements)
references
References 31 publications
6
160
2
7
Order By: Relevance
“…An almost identical oligosaccharide epitope is present on GM1, indicating the existence of molecular mimicry between the two molecules [31,44,54]. Initial studies showed that immunization of rabbits with a mixture of brain-derived gangliosides resulted in acute paralysis caused by antibody-mediated attack of axons, confirming the significance of the immune response to GM1 [55]. Subsequent studies, using a more sophisticated paradigm to test for molecular mimicry, found that Japanese white rabbits immunized with the C. jejuni LOS developed limb weakness [31].…”
Section: Guillain-barrø Syndromementioning
confidence: 94%
“…An almost identical oligosaccharide epitope is present on GM1, indicating the existence of molecular mimicry between the two molecules [31,44,54]. Initial studies showed that immunization of rabbits with a mixture of brain-derived gangliosides resulted in acute paralysis caused by antibody-mediated attack of axons, confirming the significance of the immune response to GM1 [55]. Subsequent studies, using a more sophisticated paradigm to test for molecular mimicry, found that Japanese white rabbits immunized with the C. jejuni LOS developed limb weakness [31].…”
Section: Guillain-barrø Syndromementioning
confidence: 94%
“…Mycoplasma infection has also been found to precede the disease in some cases [141]. Both in patients with AMAN [66] and in the animal model of the disease [140,158] the pathology is characterized by periaxonal macrophage attack with antibodies and activated complement deposits on the axon membrane.…”
Section: ■ Acute Motor Axonal Neuropathy (Aman)mentioning
confidence: 99%
“…This was first demonstrated for the axonal GBS variants with the establishment of an epidemiological association with preceding Campylobacter jejuni infection and the occurrence of serum anti-ganglioside antibodies [7]. The discovery that these antibodies cross-react with ganglioside-like moieties on the surface of Campylobacter jejuni laid the foundations for the subsequent studies by Yuki and other groups [3,4,15,19,20] that provided support to the intriguing hypothesis of postinfectious molecular mimicry as a cause of GBS.…”
mentioning
confidence: 89%